Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\left(3x+2\right)^2+4x-3x^2+2\left(5x-2\right)\left(5x+2\right)-75x^2\)
\(=9x^2+12x+4+4x-3x^2+50x^2-8-75x^2\)
\(=-19x^2+16x-4\)
a, \(100a^2-\left(a^2+25\right)^2=\left(10a\right)^2-\left(a^2+25\right)^2\)
\(=\left(10a-a^2-25\right)\left(10a+a^2+25\right)=-\left(a-5\right)^2\left(a+5\right)^2\)
b,\(-5\left(xy\right)^3-5\left(xy\right)^3=-10\left(xy\right)^3\)
c,\(16+2\left(xy\right)^3=2\left(2+xy\right)\left(4-2xy+x^2y^2\right)\)
a: \(\dfrac{9x^3y^2-4xy^2+5x}{2x}=\dfrac{9}{2}x^2y^2-2y^2+\dfrac{5}{2}\)
b: \(\left(\dfrac{3}{4}x^3y^6+\dfrac{6}{5}x^4y^3-\dfrac{9}{10}x^5y\right):\dfrac{-3}{5}x^3y\)
\(=y^5\cdot\left(\dfrac{3}{4}:\dfrac{-3}{5}\right)-xy^2\cdot\left(\dfrac{6}{5}:\dfrac{3}{5}\right)+\dfrac{9}{10}:\dfrac{3}{5}\cdot x^2\)
\(=\dfrac{-5}{4}y^5-2xy^2+\dfrac{3}{2}x^2\)
\(A=\left(5x+3y\right)\left(2x-3y\right)-\left(2x+3y\right)\left(5x-3y\right)\)
\(A=10x^2-15xy+6xy-9y^2-\left(10x^2-6xy+15xy-9y^2\right)\)
\(A=10x^2-15xy+6xy-9y^2-10x^2+6xy-15xy+9y^2\)
\(A=-18xy\)